The Use of Career Self-Efficacy in Mediating Career Decision Ambiguity Tolerance and Career Decision-Making Difficulties - Alexsander, Dio; Purwanto, Edy; Awalya, Awalya (Jurnal Bimbingan Konseling)
This study aimed at identifying and analyzing the relationship between career decision ambiguity tolerance and career decision-making difficulties by using self-efficacy as the mediator. The population involved in this study was Public Senior High School (SMA Negeri) students throughout Semarang City with the sample of 329 students selected using Cluster Random Sampling. Their data were collected using career decision-making difficulties scale, career decision ambiguity tolerance scale, and career self-efficacy scale. The results of direct relationship analysis showed that the ambiguity tolerance had a positive and significant relationship with career self-efficacy, and career self-efficacy had a negative and significant relationship with career decision-making difficulties. For more, the results of mediation analysis showed that there was an indirect effect between ambiguity tolerance in career decisions and the difficulties in career decision-making mediated by career self-efficacy. The implications of these findings are discussed in the discussion.